A deeper look at the dust attenuation law of star-forming galaxies at high redshift. Issue 2 (8th July 2019) - Tress, M; Ferreras, I; Pérez-González, P G; Bressan, A; Barro, G; Domínguez-Sánchez, H; Eliche-Moral, C
ABSTRACT: A diverse range of dust attenuation laws is found in star-forming galaxies. In particular, Tress et al. (2018 ) studied the SHARDS survey to constrain the NUV bump strength ( B ) and the total-to-selective ratio ( RV ) of 1753 star-forming galaxies in the GOODS-N field at 1.5 < z < 3. We revisit here this sample to assess the implications and possible causes of the correlation found between RV and B . The UVJ bicolour plot and main sequence of star formation are scrutinized to look for clues into the observed trend. The standard boundary between quiescent and star-forming galaxies is preserved when taking into account the wide range of attenuation parameters. However, an additional degeneracy – regarding the effective attenuation law – is added to the standard loci of star-forming galaxies in the UVJ diagram. A simple phenomenological model with an age-dependent extinction (at fixed dust composition) is compatible with the observed trend between RV and B, whereby the opacity decreases with the age of the populations, resulting in a weaker NUV bump when the overall attenuation is shallower (greyer). In addition, we compare the constraints obtained by the SHARDS sample with dust models from the literature, supporting a scenario where geometry could potentially drive the correlation between RV and B .